Expert System for Diagnosing Skin Diseases in Dogs using the Bayes’ Theorem Method - Nur Yanti; Mutiara Mutiara; Astri Syahputri (Jurnal Mantik, 2022)
Skin disease in dogs is the most common disease found by veterinarians. The impact of skin diseases on dogs can be aesthetically disturbing, resulting in infection and even death if left untreated a limited number of veterinarians in Indonesia compared to the number of cases of skin diseases in dogs, as well as human ignorance in identifying skin diseases in dogs, are the reasons why a system is needed that can assist in the process of diagnosing skin diseases in dogs. In the expert system, there are many methods used, one of which is the Bayes theorem method. Bayes theorem is used to calculate a decision and the right information based on observations that have been made. An expert system can replace the role of an expert whose working principle can provide definite results, as is done by an expert. This research resulted in a system application that can assist doctors in handling problems in dog skin diseases. The concept of an expert system is a program that can analyze problems and produce conclusions with the process of transferring expert knowledge into the system